2020
DOI: 10.1186/s12906-020-02932-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aged garlic extract on the atherosclerotic process – a randomized double-blind placebo-controlled trial

Abstract: Background One of the most serious secondary manifestations of Cardiovascular Disease (CVD) is coronary atherosclerosis. This study aimed to evaluate whether aged garlic extract (AGE) can influence coronary artery calcification (CAC) and to predict the individual effect of AGE using a standard process for data mining (CRISP–DM). Method This was a single-center parallel randomized controlled study in a university hospital in Europe. Patients were randomized, in a double-blind manner, through a computer-generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…This results in a product with different organoleptic characteristics, such as a darker color, sweeter taste, softer texture and less pungent flavor, making it much more attractive to consumers. Despite the differences between both of them, the consumption of black garlic has been shown to improve human health [14][15][16][17], although the mechanism of how phenolic compounds or organosulfur compounds from garlic achieve this is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…This results in a product with different organoleptic characteristics, such as a darker color, sweeter taste, softer texture and less pungent flavor, making it much more attractive to consumers. Despite the differences between both of them, the consumption of black garlic has been shown to improve human health [14][15][16][17], although the mechanism of how phenolic compounds or organosulfur compounds from garlic achieve this is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…AGE with the active ingredient S‐allylcysteine (SAC) has been shown to have a positive effect on atherosclerosis 13‐23 …”
Section: Discussionmentioning
confidence: 99%
“…In another study, aged garlic extract exerts anti-atherogenic effects in cholesterol-fed rabbits through reduction of fatty steak development, vessel wall cholesterol accumulation, and the development of fibro-fatty plaques as well as lowering the progression of coronary artery calcification (CAC) [150]. In a randomized double-blind placebo-controlled trial, aged garlic extract significantly inhibited CAC progression, lowered the levels of IL-6 glucose, and blood pressure in 104 patients at increased risk of cardiovascular events after taking 2400 mg/daily of aged garlic extract for one year [151]. Another randomized clinical trial showed that a combination of aged garlic extract and co-enzyme Q10 suppressed the CAC progression and significantly decreased carbon reactive protein levels [152].…”
Section: Black Garlic and Atherosclerosismentioning
confidence: 99%